The Value of Social and Morals Education in Verses of Work Ethos - Najib, Aan (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This Research Aims to Formulate the Concept of Social Education in The Living Verse Contained in the Qur'an. The Method of Study Used Is a Method of Thematic Interpretation To Assess The Concept of The Living Qur'an, As Well As A Method Of Sociology To Read Its Influence On The Reality of Social Life Of Society. Implementation of the Concept of Social Education in Verses About Living in the Qur'an Will Build a Spirit of Entrepreneurship, Work Ethic, Business Ethics, Responsibilities, Social Care and Victim Attitudes. IT Can Also Create Economic Growth, Revenue Distribution, Public Services, Jobs, Eliminate Poverty, Slavery, Consumptive Behavior, and Protect the Public from The Economic Crisis.